Prognostic relevance of genetic variations in T-cell acute lymphoblastic leukemia/lymphoblastic lymphoma - Yu, Hui; Du, Yuxin; Xu, Ji; Zhang, Mingzhi (Translational Cancer Research, 2019)
T-cell acute lymphoblastic leukemia (ALL) and lymphoblastic lymphoma (LBL) are highly aggressive malignant tumors. With the current intensive treatment regimens, event-free survival (EFS) rates of up to 60–90% can be achieved, but the survival rate of relapsed patients remains poor—only approximately 3–12%. Therefore, precise and effective prognostic parameters are highly needed to further improve survival rates along with reduced acute and long-term toxicities, including the rate of secondary malignancies. In addition, gene mutations can be used as therapeutic targets. This review highlights several gene mutations with a high frequency or a strong influence associated with favorable or unfavorable aspects of prognosis—NOTCH1, FBXW7, PTEN, LOH6q, CASP8AP2, c-MYC, IL-7, CALM-AF10, and CDKN2A/B—and indicates that the actual incidence of mutations in T-ALL/LBL is much higher than currently recognized. The development of multicenter clinical trials and molecular genetics research aimed at understanding the biology of these diseases offers promise for targeted and more effective therapy.